Effects of 5-alpha reductase inhibitors prior to Holmium Laser Enucleation of the prostate: Does increased adenoma density result in prolonged morcellation times? - Ganesh, Meera B.; Lee, Matthew S.; Han, Joshua G.; Assmus, Mark A.; Dean, Nicholas; Helon, Jessica W.; Krambeck, Amy E. (Frontiers in Urology, 2022)
Introduction The use of 5-alpha reductase inhibitors (5-ARIs) has been shown to improve lower urinary tract symptoms (LUTS) and decrease prostate size in men with benign prostate hyperplasia (BPH). 5-ARI therapy could increase prostate tissue density through increased collagen deposition and contraction of stromal/epithelial components. Increased tissue density could prolong morcellation times, but the effects of preoperative 5-ARI exposure on morcellation efficiency during Holmium Laser Enucleation of the Prostate (HoLEP) are not well described. Herein, we examine outcomes after HoLEP of patients on pre-operative 5-ARIs. Methods A retrospective review of patients undergoing HoLEP by an expert surgeon from Jan – Oct 2021 was performed. Student t-tests and chi-square tests were performed for continuous and categorical variables, respectively. Matched-pair analysis was performed using SPSS v28 (IBM, 2022). A p-value <0.05 was determined statistically significant. All other statistical analyses were performed using SAS v9.4 (SAS, 2019). Results A total of 322 patients underwent HoLEP during the study period and 84 patients had pre-operative 5-ARI exposure. Patients in the 5-ARI group had larger preoperative prostate size (p = 0.016). Morcellation time was longer (p=0.01), specimen weight was higher (p=0.02), and morcellation efficiency (p=0.02) was lower in the 5-ARI group. After matching, there were 67 patients in each chort (total 134) and these associations for size, morcellation time, specimen weight, and morcellation efficiency were no longer seen (p=0.8, 0.6, 0.5, and 0.7, respectively). Furthermore, no associations between 5-ARI and post-operative admissions or ED visits were noted. Conclusion In this retrospective study, preoperative use of 5-ARIs did not affect enucleation or morcellation efficiency. Thus, preoperative 5-ARI therapy does not appear to alter outcomes after HoLEP.